2021
DOI: 10.3390/diagnostics11112119
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Consensus Clustering Approach for Hospitalized Patients with Dysmagnesemia

Abstract: Background: The objectives of this study were to classify patients with serum magnesium derangement on hospital admission into clusters using unsupervised machine learning approach and to evaluate the mortality risks among these distinct clusters. Methods: Consensus cluster analysis was performed based on demographic information, principal diagnoses, comorbidities, and laboratory data in hypomagnesemia (serum magnesium ≤ 1.6 mg/dL) and hypermagnesemia cohorts (serum magnesium ≥ 2.4 mg/dL). Each cluster’s key f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Previous studies reported the incidence of hypomagnesemia among hospitalized patients ranged between 11.0-20.0% [ 6 , 7 ], and it was increased to 65.0% in critically ill patients [ 6 , 9 ]. The observed discrepancies in reported incidences may be attributed to variations in the selection of cutoff values and the diverse clinical characteristics exhibited by the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported the incidence of hypomagnesemia among hospitalized patients ranged between 11.0-20.0% [ 6 , 7 ], and it was increased to 65.0% in critically ill patients [ 6 , 9 ]. The observed discrepancies in reported incidences may be attributed to variations in the selection of cutoff values and the diverse clinical characteristics exhibited by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The normal reference range for total Mg concentration is between 0.7 and 1.0 mmol/L [ 5 ]. Mg disorders are widespread in hospitalized patients, particularly hypomagnesemia, which occurs in 10–24% of them [ 6 , 7 ]. Hypomagnesemia is more common (65%) in patients admitted to intensive care units [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We determined the clusters' key features using an absolute standardized mean difference (SMD) of > 0.3 in reference to Thongprayoon's studies [22][23][24]. We then compared outcomes among the identi ed clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus matrix heat map (k = 10) depicting consensus values on a white to blue color scale of each cluster. References [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] are cited in the supplementary materials. Data Availability Statement: Data will be made available by the authors upon reasonable request.…”
Section: Supplementary Materialsmentioning
confidence: 99%